Analisis Tindak Tutur Representatif dalam Daftar Putar Video “Tips dan Edukasi” pada Kanal YouTube Zahid Ibrahim - Hening Jati Melani; Sabrina Fadilatul Khoiroh; Anggun Rizka Ramadania; Sakna Cahyani; Leyvisca Kristi Nugroho; Muhamad Syafiq Asyam; Asep Purwo Yudi Utomo; Arum Yuliya Lestari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Language is one of the tools used for communication. Speech acts employ language as a form of complex communication that considers the context, the speaker’s intent, and the expected reactions to understand the meaning and purpose of each utterance. This research describes the analysis of representative speech acts in the